Solid-Liquid Phase Equilibrium of the n-Nonane plus n-Undecane System for Low-Temperature Thermal Energy Storage - Sequeira, Maria C. M.; Nikitin, Timur; Caetano, Fernando J. P.; Diogo, Herminio P.; Fareleira, Joao M. N. A.; FAUSTO, RUI (Springer/Plenum Publishers, 2024)
The current article presents an exploration of the solid-liquid phase diagram for a binary system comprising n-alkanes with an odd number of carbon atoms, specifically n-nonane (n-C-9) and n-undecane (n-C-11). This binary system exhibits promising characteristics for application as a phase change material (PCM) in low-temperature thermal energy storage (TES), due to the fusion temperatures of the individual components, thereby motivating an in-depth investigation of the solid-liquid phase diagram of their mixtures. The n-nonane (n-C-9) + n-undecane (n-C-11) solid-liquid phase equilibrium study herein reported includes the construction of the phase diagram using Differential Scanning Calorimetry (DSC) data, complemented with Hot-Stage Microscopy (HSM) and low-temperature Raman Spectroscopy results. From the DSC analysis, both the temperature and the enthalpy of solid-solid and solid-liquid transitions were obtained. The binary system n-C-9 + n-C-11 has evidenced a congruent melting solid solution at low temperatures. In particular, the blend with a molar composition x(undecane) = 0.10 shows to be a congruent melting solid solution with a melting point at 215.84 K and an enthalpy of fusion of 13.6 kJmol(-1). For this reason, this system has confirmed the initial signs to be a candidate with good potential to be applied as a PCM in low-temperature TES applications. This work aims not only to contribute to gather information on the solid-liquid phase equilibrium on the system n-C-9 + n-C-11, which presently are not available in the literature, but especially to obtain essential and practical information on the possibility to use this system as PCM at low temperatures. The solid-liquid phase diagram of the system n-C-9 + n-C-11 is being published for the first time, as far as the authors are aware.
Keywords: Energy Storage; Low Temperature; Odd n-alkanes; Phase Change Material (PCM); Solid–liquid Phase Diagram